2019
DOI: 10.1002/1348-9585.12102
|View full text |Cite
|
Sign up to set email alerts
|

Baropodometric evaluation of foot load distribution during gait in the group of professionally active nurses

Abstract: Healthcare workers often declare poor knowledge and non-application of ergonomic principles. 1 The most common reasons are lack of knowledge related to the need to apply ergonomic principles at work, haste or carelessness. Nurses often work with lifting and carrying loads that exceed the body's adaptability. 2 It is likely that choosing more precise content related to traffic ergonomics and safe behavior during the Occupational Health and Safety (OSH) Training,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…By explanation, nurses working for more than 20 years complained about various musculoskeletal overloads due to their many years of hard work in this challenging profession. Our previous study revealed that 68% of nurses stated that they knew the principles of work ergonomics, but only 14% acknowledged that they always applied them, 62% sometimes applied them, and as many as 24% did not follow the principles of ergonomics at work, despite their awareness (Kołcz, Główka, Kowal, & Paprocka‐Borowicz, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…By explanation, nurses working for more than 20 years complained about various musculoskeletal overloads due to their many years of hard work in this challenging profession. Our previous study revealed that 68% of nurses stated that they knew the principles of work ergonomics, but only 14% acknowledged that they always applied them, 62% sometimes applied them, and as many as 24% did not follow the principles of ergonomics at work, despite their awareness (Kołcz, Główka, Kowal, & Paprocka‐Borowicz, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, provision of lifting equipment (with appropriate training) in hospitals failed to reduce the risk of low back pain in nurses, 71 and at least one of the explanations is that the lifting aids are not always used or are not used as intended. 44 Numerous studies report that workplace factors explain just a small proportion of the risk of disabling pain (typically 10%-20%). 18 Although some of the remainder of the risk of pain remains unexplained, another important element of the risk is attributable to personal factors.…”
Section: Occupational Health Perspectivementioning
confidence: 99%
“…For example, provision of lifting equipment (with appropriate training) in hospitals failed to reduce the risk of low back pain in nurses, 71 and at least one of the explanations is that the lifting aids are not always used or are not used as intended. 44…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the usefulness of the baropodometric platform to diagnose several diseases on plantar pressure [ 11 , 12 , 13 , 14 ]. Feet are essential in the stability and propulsion of the human being [ 15 ].…”
Section: Introductionmentioning
confidence: 99%